To work this out you have (6x^2 - 19x - 85) = (2x - 5)(ax + b)
-5b must equal -85
b = 17
2a must equal 6
a = 3
(6x^2 - 19x - 85) = (2x - 5)(3x + 17)
Check
-15x + 34x = 19x correct
So (2x - 5)(3x + 17) is width times length
width = (3x + 17)cm
2006-12-14 13:26:46
·
answer #1
·
answered by Tom :: Athier than Thou 6
·
1⤊
0⤋
Remember that the area of a rectangle is the following:
A = Length times Width.
We're given the length is 2x+5, and we're given the area A is 6x^2 - 19x - 85.
Therefore, if we call the width W, and if
A = LW
Then
6x^2 - 19x - 85 = (2x + 5)W
Divide both sides by 2x + 5 to get
[6x^2 - 19x - 85]/[2x + 5] = W
To solve this, we need to factor the numerator. Through trial and error, you'll find that it factors into (2x + 5) (3x - 17). Therefore
{(2x + 5) (3x - 17)} / [2x + 5] = W
Factors on the numerator and denominator cancel each other out, leaving you with
3x - 17 = W, which is our width.
HOWEVER, we must keep in mind that during the steps of our algebra, we divided by (2x + 5) to get where we wanted to go. Division by 0 is a big no-no (and is certainly not allowed in math), so we have give an added restriction: 2x + 5 cannot equal 0. If we solve for x in the equation 2x + 5 = 0, then
2x + 5 = 0
2x = -5
x = -5/2
Therefore, our solution would be W = 3x - 17, for x not equal to -5/2.
Do we need this added restriction? Maybe not, because we know that width is positive. That is,
3x - 17 >= 0, so
3x >= 17, and
x >= 17/3
Our values for x are greater than 17/3 anyway (so there's no need for a restriction).
2006-12-14 13:33:07
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
You wrote 2x = 5 instead of 2x + 5...
6x^2 - 19 x - 85 =
I have to found 2 numbers so that their difference is 19 and their product is 510.
- 85 x 6 = - 510. This - sign means that one of the numbers have to be negative
Considering that the difference, the numbers must be pretty close to each other.
510 = 1 x 510 = 2 x 255 = 3 x 170 = 5 x 102 = 6 x 85 = 10 x 51 = 15 x 34, etc.
510 = 2 x 3 x 5 x 17
15 x 34 seems to be OK. 34 - 15 = 19
So, now do this:
6x^2 - (34 - 15) x - 85 = 6x^2 + 15 x - 34 x - 85 = 3x (2 x + 5) - 15 (2x+5)
Since 2x + 5 is a common factor, then the result is (3x-15)(2x+15)
Anabel
2006-12-14 13:36:01
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
width=area/length
=6x^2-19x-85/2x+5
2006-12-14 13:25:43
·
answer #4
·
answered by raj 7
·
0⤊
0⤋
if 2x+5 it is 3x-17. Follow Tom's example above but be careful that you check to multiple the two factors back together
2006-12-14 13:30:11
·
answer #5
·
answered by samsosa2000 2
·
0⤊
0⤋
Is that supposed to be 2x+5 or 2x-5
2006-12-14 13:28:08
·
answer #6
·
answered by Film XPress 1
·
0⤊
0⤋